Pembuatan Simplisia Rimpang-rimpangan dan Dorongan Pembentukan Ukot Umot pada Kelompok Tani Desa Lempake Samarinda - Sulistiarini, Riski; Nisaa, Nur Rezky Khairun; Farah, Harra Ismi; Arifian, Hanggara; Meylina, Lisna; Rijai, Akhmad Jaizzur; Prasesti, Gayuk Kalih (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The community service activity themed "Preparation of Rhizome Simplisia and Encouragement for the Formation of Ukot Umot in the Farmer Group of Lempake Village, Samarinda" aimed to increase public knowledge about the preparation of high-quality rhizome simplisia and to encourage the establishment of local institution-based organizations (Ukot Umot). The activity involved farmer groups, women's PKK groups, and village officials. The materials presented included stages of washing, cutting, drying, and storing simplisia. Additionally, a participatory discussion on the importance of Ukot Umot institutions was conducted to strengthen collaboration and improve market access. Based on an evaluation through a questionnaire, 100% of participants stated that the activity was highly beneficial, with high satisfaction levels regarding the relevance of the material, the delivery method, and the benefits of the activity. The initial impacts of the activity included increased participant knowledge, a commitment to forming Ukot Umot, and motivation to process rhizomes independently. Despite challenges such as limited facilities, this activity successfully laid the foundation for the sustainable development of rhizome-based businesses.